ISLAMIC STATE INSTITUTE OF BUKITTINGGI STUDENTS’ SATISFACTION ON ACADEMIC ATMOSPHERE AND SERVICE - Sesmiarni, Zulfani; Ilmi, Darul (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2019)
Abstract: This research is inspired from the researcher’s motivation to see the satisfaction of IAIN Bukittinggi students in terms of academic atmosphere and services. This study was conducted at IAIN Bukittinggi students as population. The sample of research were 438 students. Data collection techniques used in this study were questionnaires to measure satisfaction, academic’s atmosphere, and academic services. From the research data, there is a significant influence of Academic Atmosphere on Student’s Satisfaction at IAIN Bukittinggi with significant level of 5%. Furthermore, there is a significant influence of the Academic Service on Student’s Satisfaction at IAIN Bukittinggi with significant level of 5%. Then, there is a significant influence of academic atmosphere on academic services at the level of 5%. Finally, there is influence of academic atmosphere and academic service in accordance to student’s satisfaction at level of 5%. Abstrak: Penelitian ini diawali dengan adanya motivasi penulis untuk melihat kepuasan mahasiswa IAIN Bukittinggi ditinjau dari aspek suasana dan pelayanan akademik. Penelitian ini dilakukan di IAIN Bukittinggi dengan populasi mahasiswa, dengan sampel sebanyak 438 orang. Teknik pengumpulan data dalam penelitian ini adalah dengan kuesioner untuk mengukur kepuasan, suasana dan pelayanan akademik. Dari data penelitian maka terdapat pengaruh yang signifikan suasana akademik terhadap kepuasan mahasiswa di IAIN Bukittinggi pada taraf signifikan 5 %. Selanjutnya terdapat pengaruh yang signifikan layanan akademik terhadap Kepuasan mahasiswa di IAIN Bukittinggi pada taraf signifikan 5%. Kemudian terdapat pengaruh yang signifikan suasana akademik pengaruh terhadap layanan akademik pada taraf 5%. Terakhir terdapat pengaruh suasana akademik dan layanan akademik secara bersama-sama hubungan terhadap kepuasan mahasiswa pada taraf 5%.